Initial experiments of the flow field around cross-country skiers - Larsson, I. A. S.; Lycksam, H.; Ainegren, M. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Aerodynamics is the study of air flowing around solid bodies, where the link between velocity and pressure distribution and the resulting aerodynamic loads are of special interest. In sports, aerodynamics plays a crucial role since the drag force is a major obstacle to overcome in several different disciplines, xc-skiing being one of them. Much effort is spent studying the aerodynamics of speed sports such as speed skiing and cycling with detailed measurements of both the velocity field and pressure distribution. Aerodynamic drag in xc-skiing and its resulting effect on skiers` physiology has been studied to some extent, but not linked to the flow field itself 1,2.